Heil humor: rir do nazismo é o melhor remédio. oder? humor antinazista e possíveis impactos no ensino de língua e cultura alemã - Porto Neto, Harry José do (2018)
This study is motivated by the interest of teaching German as a foreign language in the Brazilian context, allied to political humor, specifically antinazi and antifascist humor. Nowadays, in Germany, this kind of humor appears on movies as “Er ist wieder da”, series, youtube channels, books, newspapers, also spread by the satiric political party Die Partei via several media. Although laughing at Nazism might be polemic, it can be educative. The objective of this study (with the aim of usage of authentic texts to bring the cultural aspect of political humor in Germany) is, then, to understand how authentic texts that ridicules Hitler, with antinazist humor can be present in classes and in textbooks of German as foreign language, based on opinions of experienced teachers of teaching of German culture and language. In order to understand how humor works in different contexts, first I searched for theories about laugh, carnivalization, humor and its social functions, as well previous studies about political humor during the III Reich with the purpose of laugh at and against Nazism. The analysis shows that political humor that ridicules Hitler and his prejudicial ideologies can educate and point out the danger of a possible return of fascism. Although this kind of humor is present on several German media, in the nowadays society, it is not sufficiently explored in classes on Brazilian context, unknown for the most, misunderstood, disapproved and still treated with prejudice by institutions responsible for the teaching of German as foreign language.